Electromagnetic interference effect of dental equipment on cardiac implantable electrical devices: A systematic review. Issue 12 (12th September 2020) - Niu, Yuting; Chen, Yufei; Li, Wenjing; Xie, Ruiqin; Deng, Xuliang
Abstract: Background: The electromagnet interference (EMI) effect resulting from using dental equipment near cardiovascular implantable electronic devices (CIEDs) is controversial based on in vitro and in vivo studies. We aimed to summarize the available evidence to investigate the safety of using dental equipment on patients with CIEDs. Methods: An electronic search was performed in PubMed, Embase, MEDLINE Ovid, and the Cochrane Library for relevant studies published between January 2000 and May 2020. The search strategy centered on terms related to dental devices and CIEDs. Two independent reviewers determined the final inclusion of the studies in the systematic review. The EMI effect was summarized based on different dental instruments detected in in vitro or in vivo studies. Results: The primary search identified 84 articles, and 18 studies were finally included in this systematic review after exclusions. Most in vitro studies (n = 12) reported background noise or severe EMI affecting CIED function at a close distance from the lead tip or at a high sensitivity setting of CIEDs. In in vivo studies (n = 6), EMI that altered CIED function was not detected at clinical distance and sensitivity settings. The summary, based on electronic apex locators, ultrasonic devices, and electric pulp testers, demonstrated the compatibility of these common dental devices with CIEDs. Conclusions: This systematic review indicates that most dental instruments can be used safely in routine dental practice. The EMI effect of dental equipment depends on the exposure distance and lead‐related parameters of the CIEDs.